2017
DOI: 10.1177/1715163517734236
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with chronic HIV care provided through an innovative pharmacist/nurse-managed clinic and a multidisciplinary clinic

Abstract: Patients are satisfied with both clinics, supporting NPC as an innovative model for chronic HIV care. Comparison of outcomes between clinics is needed to ensure high-quality care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…As a result, nurses tend to act as the organizers, planners, and implementers in the rehabilitation of patients. Some studies suggested that a nurse-led MDT may be able to guarantee a fixed leader, enhance the tightness of the team, and play a coordinating role in the transitional care process of standardization and implementation [18,19]. Therefore, this study intended to develop a nurse-led MDT model in AS transitional care and to assess its effects on clinical outcomes and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, nurses tend to act as the organizers, planners, and implementers in the rehabilitation of patients. Some studies suggested that a nurse-led MDT may be able to guarantee a fixed leader, enhance the tightness of the team, and play a coordinating role in the transitional care process of standardization and implementation [18,19]. Therefore, this study intended to develop a nurse-led MDT model in AS transitional care and to assess its effects on clinical outcomes and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of high patient satisfaction appear to be consistent across disciplines with comparable results reported in multidisciplinary HIV, pediatric allergy, rheumatic disease, interstitial lung disease, and gender dysphoria clinics. 20-23…”
Section: Discussionmentioning
confidence: 99%
“…The provincial HIV Clinic is located in St. John's, NL, and provides specialized medical services to PLHIV in the province. The HIV clinic consists of a multidisciplinary team including a physician (infectious disease specialist/internist), nurse practitioner, a social worker and pharmacist who provide care to PLHIV throughout NL, and see each patient approximately every 6-12 months [13]. At the time of this study, the clinic had manual charts including individual-level medication and healthcare information for PLHIV who receive healthcare services via the clinic.…”
Section: Hiv Clinic Datamentioning
confidence: 99%
“…In Newfoundland and Labrador, PL-HIV primarily receive both specialist and primary care through an interdisciplinary HIV specialty clinic. More recently, some have questioned whether specialists are appropriately addressing the primary care needs of PLHIV [10][11][12][13]. Adding family physicians to the continuum of care has the potential to greatly impact the health outcomes and quality of life of PL-HIV given the level of care required to effectively manage the other chronic conditions they experience [11,12].…”
Section: Introductionmentioning
confidence: 99%